Outcomes of Treatment in Patients with Elderly Postmenopausal Osteoporosis: Comparision of Oral and Parenteral Bisphosphonates - Ahmet Aslan; Anıl Gülcü; Ahmet Özmeriç (Galenos Yayinevi, 2018)
Objective: In this study, we aim to compare the efficacy of oral and parenteral bisphosphonates used in postmenopausal osteoporosis (OP)treatment. Materials and Methods: Between 2010 and 2015, patients older than 65 years who were diagnosed with postmenopausal OP and treated with oral or parenteral bisphosphonate were included in the study. According to treatment, 72 patients receiving oral bisphosphonate and 52 patients receiving parenteral bisphosphonate were divided into two groups as group O and group P respectively. The results of the second year treatment of 124 patients who were treated regularly and at least two years follow up were evaluated and compared. Results: According to the pre-treatment state in both groups; bone mineral density (BMD) of vertebral and femoral, and T-scores showed significant improvement. The mean improvement in vertebral and femoral T-scores and femoral BMD values was better in group P and there was statistically significant difference. In the oral bisphosphonate group, there was a statistically significant difference between the groups in favor of alendronate in the femoral T-score and the improvement in the vertebral and femoral T-score in the parenteral bisphosphonate group was better in the zoledronate subgroup and statistically significant. Conclusion: The results of this study demonstrate that oral and parenteral bisphosphonates are effective in the treatment of postmenopausal OP. Nevertheless, parenteral bisphosphonates were found to be more effective in terms of vertebral and femoral T-scores and femoral BMD average improvement.